2015
DOI: 10.1371/journal.pone.0142188
|View full text |Cite
|
Sign up to set email alerts
|

Rasch Analysis of the Adult Strabismus Quality of Life Questionnaire (AS-20) among Chinese Adult Patients with Strabismus

Abstract: BackgroundThe impact of strabismus on visual function, self-image, self-esteem, and social interactions decrease health-related quality of life (HRQoL).The purpose of this study was to evaluate and refine the adult strabismus quality of life questionnaire (AS-20) by using Rasch analysis among Chinese adult patients with strabismus.MethodsWe evaluated the fitness of the AS-20 with Rasch model in Chinese population by assessing unidimensionality, infit and outfit, person and item separation index and reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Correction of strabismus offers improvement in psychosocial functioning. [ 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 ] In a study by Menon et al .,[ 21 ] 95% of participants reported positive changes in appearance, self-confidence, self-esteem, and relationship with friends after being treated for strabismus. However, they found no influence of the type of strabismus on the problems perceived by their study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Correction of strabismus offers improvement in psychosocial functioning. [ 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 ] In a study by Menon et al .,[ 21 ] 95% of participants reported positive changes in appearance, self-confidence, self-esteem, and relationship with friends after being treated for strabismus. However, they found no influence of the type of strabismus on the problems perceived by their study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Adult Strabismus‐20 (AS‐20) questionnaire (Original [n = 24], Adapted [n = 1], Chinese [n = 4], Danish [n = 1])…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 25 translated the AS-20 into Chinese and then performed Rasch analysis on responses from a cohort of 247 adult patients with strabismus. 26 In both Rasch studies, the AS-20 was found to be unidimensional when analyzing the two original constructs (psychosocial and function) separately, although there were some slight differences in misfitting items and category response when compared to the Rasch analysis of the English version. Such differences are not unexpected given different cultural backgrounds and clinical characteristics (e.g., 70% of subjects with exotropia in the Chinese study 26 ).…”
Section: Discussionmentioning
confidence: 98%
“… 26 In both Rasch studies, the AS-20 was found to be unidimensional when analyzing the two original constructs (psychosocial and function) separately, although there were some slight differences in misfitting items and category response when compared to the Rasch analysis of the English version. Such differences are not unexpected given different cultural backgrounds and clinical characteristics (e.g., 70% of subjects with exotropia in the Chinese study 26 ). Different lookup tables for non-English versions of the AS-20, such as those provided by Gothwal et al 24 , may be needed, particularly any time significant differences in performance are highlighted by Rasch analysis in different cultures.…”
Section: Discussionmentioning
confidence: 98%